2022
DOI: 10.3389/fimmu.2022.812164
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Benzene-Indol Derivative Alleviates LPS-Induced Acute Lung Injury Through Inhibiting the NLRP3 Inflammasome

Abstract: Acute lung injury (ALI) is a common complication of critical illness that could frequently lead to acute respiratory distress syndrome and other serious clinical consequences. Sepsis is one of the major and most common inducements among all causes of ALI. Due to its high incidence and mortality rate and also the complexity in treatment, sepsis-related ALI has become an urgent clinical problem waiting to be solved effectively. At present, only the protective ventilation strategy, restrictive fluid management, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Based on these studies and analyses, we hypothesize that the observed reduction in COPD risk may be attributable to the compensatory or metabolic pathways activated when these compounds reach certain concentrations within the body. In conclusion, while the precise mechanism linking blood benzene and o-xylene concentrations to COPD risk remains to be elucidated, potential factors such as metabolic pathway involvement and antioxidant activity warrant further investigation to validate these hypotheses ( 35 , 36 ). Furthermore, elevated levels of education and income may be associated with residing in urban areas with high pollution levels, concurrently experiencing increased stress in living and working conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Based on these studies and analyses, we hypothesize that the observed reduction in COPD risk may be attributable to the compensatory or metabolic pathways activated when these compounds reach certain concentrations within the body. In conclusion, while the precise mechanism linking blood benzene and o-xylene concentrations to COPD risk remains to be elucidated, potential factors such as metabolic pathway involvement and antioxidant activity warrant further investigation to validate these hypotheses ( 35 , 36 ). Furthermore, elevated levels of education and income may be associated with residing in urban areas with high pollution levels, concurrently experiencing increased stress in living and working conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous lines of evidence indicate that exposure to LPS stimulation can elicit an inflammatory response and other pulmonary lesions, ultimately leading to the development of respiratory disorders. Serious pulmonary infection involved with LPS is a high risk factor for ALI/ARDS, which can cause inflammatory cells to recruit into the lung, an increase in capillary permeability, and alveolar edema [ 24 , 25 , 26 ]. The morphological changes caused by LPS were significant inflammatory cell infiltration, alleviation by hemorrhage, and thickness of the alveolar wall after the Lut treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An et al used quantitative realtime reverse transcription-polymerase chain reaction (qRT-PCR) and western blotting (WB) to establish that ADSC-Exos overexpressing miR-21 up-regulated HIF-1a, VEGF, SDF-1, p-AKT, and p-ERK1/2 while down-regulating PTEN. These findings suggest that miR-21-enriched ADSC-Exos promote angiogenesis through the activation of AKT and ERK and the expression of HIF-1a and SDF-1 (176). miR-125a-3p in ADSC-Exos can also promote wound healing and angiogenesis in mice by inhibiting PTEN in the granulation tissue of wounds (177).…”
Section: Angiogenesismentioning
confidence: 99%